2015
DOI: 10.1039/c4ta05819d
|View full text |Cite
|
Sign up to set email alerts
|

Formation chemistry of perovskites with mixed iodide/chloride content and the implications on charge transport properties

Abstract: We study the formation chemistry of Cl-doped perovskites by examining the chemical interactions between thermally evaporated MAI and PbCl2through X-ray photoemission spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 29 publications
18
95
0
Order By: Relevance
“…Other works have claimed the presence of chloride within the physical perovskite structure as MAPbI 3−x Cl x to be incorrect, and believe it remains as unconverted PbCl 2 that serves as nucleation sites to improve surface coverage of the perovskite film [42,69]. Currently, chlorine incorporation has been investigated in the context of perovskite film growth in order to reveal the mechanisms that govern improved device performances [68][69][70][72][73][74]. It has been suggested that crystallization begins from the nucleation of complex ion aggregates due to the limited solubility of the chlorine containing precursors, e.g.…”
Section: 'B' Sitementioning
confidence: 97%
“…Other works have claimed the presence of chloride within the physical perovskite structure as MAPbI 3−x Cl x to be incorrect, and believe it remains as unconverted PbCl 2 that serves as nucleation sites to improve surface coverage of the perovskite film [42,69]. Currently, chlorine incorporation has been investigated in the context of perovskite film growth in order to reveal the mechanisms that govern improved device performances [68][69][70][72][73][74]. It has been suggested that crystallization begins from the nucleation of complex ion aggregates due to the limited solubility of the chlorine containing precursors, e.g.…”
Section: 'B' Sitementioning
confidence: 97%
“…Hu et al [26] demonstrated an inverted HTM-free PHJ perovskite solar cell with a simple thermal evaporated perovskite/C 60 bilayer structure, which presented a PCE of 5.4%. Ng et al [27] reported that the PCE can be increased to 6.1% via adopting 4,7-diphenyl-1,10-phenanthroline (Bphen) as the hole blocking layer. However, their PCEs are still lower and should be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite films can be prepared by solution process via one-step or two-step solution depositions [2,3] and vacuum thermal evaporation [4,[26][27][28]. Among these methods, the vacuum thermal evaporation forms a perovskite film with the most homogeneous morphology and the highest coverage, leading to a higher PCE of the corresponding devices.…”
Section: Introductionmentioning
confidence: 99%
“…The formation chemistry of co-evaporated CH 3 NH 3 PbI 3(1−y) Cl 3y was examined utilizing in situ X-ray photoelectron spectroscopy (XPS). 52 A negligible amount of Cl was detected due to the ionic radii mismatch between Cl and I ions. Borchert et al employed in situ XRD to record the growth and thermal annealing of co-evaporated MAPbI 3 and MAPbI 3(1−y) Cl 3y .…”
mentioning
confidence: 99%